TRANSFOMASI EKONOMI MUSTAHIK MELALUI ZAKAT PRODUKTIF : ANALISIS PROGRAM BAZNAS KABUPATEN PACITAN - Darwisy, Muhammad; Ma`ruf, Syaiful; Sustiawan, Asis (Investama : Jurnal Ekonomi dan Bisnis, 2025)
Changes in economic status and business improvement are expectations for business actors, one of the government institutions that participate in encouraging the economic growth of the community is BAZNAS. BAZNAS Pacitan Regency has a social program called Productive Zakat, there are two types of financing provided to mustahik, namely the Business Rombong Program and Revolving Funds. The purpose of this study is the extent to which the impact of the productive zakat program in transforming the economy of mustahik in Pacitan Regency for the better. The lack of financial capital, expertise, and creativity is the main problem experienced by mustahik. This type of research is field research, the method used is descriptive qualitative, for the data used in this research consists of primary data and secondary data. Primary data was obtained from interviews with BAZNAS Pacitan Regency and mustahik recipients of the Productive Zakat program. Secondary data was obtained from BAZNAS program reports, some literature, articles from magazines, journals and newspapers on the internet. The results showed that the implementation of productive zakat programs, both revolving fund programs and business rombong, had a positive impact on mustahik business growth, increased income and gave birth to new entrepreneurs. The productive zakat utilization program carried out by BAZNAS Pacitan Regency has been running well. However, it needs to be improved again, one of which is in terms of socialization to the community.